A study on quality of front office counter service at Alor Setar Holiday Villa / Norsalbiah Saad - Saad, Norsalbiah (1998)
This research is about a study on quality of front office counter service at Alor Setar Holiday Villa. It scrutinized the level of quality front office counter service at Alor Setar Holiday Villa have that is perceived by Alor Setar Holiday Villa guests during their visit or stay at the hotel. In measuring the quality of front office counter service at Alor Setar Holiday Villa, five variables had been identified. The five variables are warm attendance, immediate attendance, co-operation, personality, and courtesy communication. Finding shows that the five variables are the important elements in providing quality counter service, especially at the hospitality industry. In order for the company to enhance their quality of front office counter service the management of the company should emphasize on this five elements. Besides it also can be effectively done through a proper and continuous training and etc.